Sturge Weber Syndrome: An Unusual Case with Multisystem Manifestations - Nidhi, C (Ethiop J Health Sci, 2016)
BACKGROUND: Sturge-Weber syndrome (SWS) is a rare congenital neurocutaneous disorder. It is characterized by the presence of facial port wine stains, neurological abnormalities like seizures and mental retardation, ocular disorders, oral involvement and leptomeningeal angiomas. CASE REPORT: A 13-year-old boy presented with the chief complaint of swollen, bleeding gums and deposits on the teeth. Detailed medical and dental history, clinical examination and investigations confirmed the diagnosis of Sturge-Weber syndrome. The treatment comprised of a thorough plaque control regimen to reduce the gingival enlargement, and it included oral hygiene instructions, thorough scaling, root planing at regular intervals and plaque index scoring which motivated the patient at each visit. CONCLUSION: This case illustrates that early intervention in a patient with Sturge-Weber syndrome is quintessential because of its associated gingival vascular features and their complicating manifestations. Furthermore, the need for periodic oral examinations and maintenance of good oral hygiene to prevent any complications from the oral vascular lesions has been highlighted.